2017
DOI: 10.1016/j.nimb.2017.05.055
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-energy proton irradiation on the electrical characteristics of Au/Ni/4H-SiC Schottky barrier diodes

Abstract: Au/Ni (20:80) Schottky barrier diodes (SBDs) were resistively evaporated on nitrogen-doped n-type 4H-SiC. Current-voltage (I-V) and capacitance-voltage (C-V) characteristics of the SDBs were investigated before and after bombardment with 1.8 MeV proton irradiation at a fluence of 2.0 × 10 12 cm -2 . The measurements were carried out in the temperature range 40 -300 K in steps of 20 K. Results obtained at room temperature (300 K) showed highly rectifying devices before and after bombardment. It was observed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The different polytypes of SiC only differ in the stacking order which affects their electronic and optical properties. Earlier reports have shown that all polytypes are inert, hard and have high thermal conductivity [1,2]. Furthermore, the breakdown electric field strength, saturated drift velocity or impurity ionization energies are all specific for different polytypes.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The different polytypes of SiC only differ in the stacking order which affects their electronic and optical properties. Earlier reports have shown that all polytypes are inert, hard and have high thermal conductivity [1,2]. Furthermore, the breakdown electric field strength, saturated drift velocity or impurity ionization energies are all specific for different polytypes.…”
Section: Introductionmentioning
confidence: 98%
“…The 4H-SiC is a promising material for high-voltage devices due to its higher bulk mobility and smaller anisotropy compared to other polytypes. The 4H-SiC has been experimentally reported to have a wide band gap of 3.26 eV at 300 K. In addition, the 4H-SiC is capable of operating at high temperature and high frequency which makes it a suitable substrate mat erial for producing high frequency electronic devices for applications in radiation harsh environments (space, accelerator facilities and nuclear power plants) [1,2]. Point and extended defects play vital roles in 4H-SiC as they have the tendency to either influence or limit its performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The transport of carriers across the M-S interface is influenced by the junction barrier potential. Therefore, it is of significant importance to study the current transport properties of the M-S interface and its modification for a better understanding of the operations of electronic devices [3,4].…”
Section: Introductionmentioning
confidence: 99%